2007
DOI: 10.1891/088667007782793138
|View full text |Cite
|
Sign up to set email alerts
|

Women’s Experiences of Male-Perpetrated Sexual Assault by Sexual Orientation

Abstract: This study examined differences in male-perpetrated adult sexual assault experiences among women of various sexual orientations using a large urban convenience sample (N = 1,022). Results showed many similarities in disclosure to others, perceived helpfulness, and attributions of blame, but there were also differences by sexual orientation. Heterosexual women were more likely to experience completed sexual assault than lesbian or bisexual women. Lesbians were more likely to be assaulted by relatives than bisex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
109
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(119 citation statements)
references
References 49 publications
(82 reference statements)
9
109
0
Order By: Relevance
“…LGBQ students were also significantly more likely to be the victim of at least one act of sexual contact when too intoxicated to consent, which mirrors Martin et al's (2011) finding that lesbian and bisexual college women experienced significantly higher rates of incapacitated sexual violence than heterosexual college women. Our findings suggest that LGBQ college students are at an increased risk for sexual violence, particularly when substance use is involved.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…LGBQ students were also significantly more likely to be the victim of at least one act of sexual contact when too intoxicated to consent, which mirrors Martin et al's (2011) finding that lesbian and bisexual college women experienced significantly higher rates of incapacitated sexual violence than heterosexual college women. Our findings suggest that LGBQ college students are at an increased risk for sexual violence, particularly when substance use is involved.…”
Section: Discussionsupporting
confidence: 56%
“…Martin, Fisher, Warner, Krebs, and Lindquist (2011) conducted a study of lesbian, bisexual, and heterosexual female university students to compare rates of sexual violence. The researchers found that bisexual women (13.5%) experienced significantly higher rates of physically forced sexual violence than heterosexual women (4.4%) during their time at university.…”
Section: Rates Of Sexual Violence Among Lgbq and Heterosexual Collegementioning
confidence: 99%
“…In most cases, these studies neglect to probe for information regarding processes of sexual identity development and personal sexual histories, often rendering heterosexuality invisible. When (hetero)sexual behavior is examined, it is surrounded by discussions of risk, especially in a "hook-up" culture, with a focus on casual sex, contraception, sexually transmitted infections/diseases, substance (ab)use, and threat of sexual assault (e.g., Hughes, Johnson, & Wilsnack, 2001;Jackson, 2005;Lambert, Kahn, & Apple, 2003;Long, Ullman, Long, Mason, & Starzynski, 2007;Reddy & Dunne, 2007;Roberts, Auinger, & Klein, 2006). When not interested in sexual behavior per se, research on women's (hetero)sexual development tends to focus on gender instead; for example, the negotiation of and attitudes toward limiting gender roles, gendered heterosexual scripts, sexual double standards, and the socialization of femininity (e.g., Jackson & Cram, 2003;Kim, Sorsoli, Collins, Zylbergold, Schooler, & Tolman, 2007;Morgan & Zurbriggen, 2007;Striepe & Tolman, 2003).…”
mentioning
confidence: 99%
“…Far from coalescing into a single traumatic experience, the trauma that bisexual people experience may be experienced as an accumulation of chronic mislabelling, invisibility and erasure, negative stereotyping, social exclusion, and challenges to the authenticity of their identity. Limited evidence suggests that PTSD is elevated in the bisexual population (Alessi, Meyer, & Martin, 2013;Long, Ullman, Long, Mason, & Starzynski, 2007;Roberts, Austin, Corliss, Vandermorris, & Koenen, 2010).…”
Section: Introduction Posttraumatic Stress Disorder From the Dsm-iv Tmentioning
confidence: 99%